2022
DOI: 10.1016/j.carrev.2021.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Association Between the COVID-19 Ad26.COV2.S Vaccine and Acute Myocarditis: A Case Report and Literature Review

Abstract: With the recent approval and widespread administration of the Pfizer-BioNTech, Moderna, and Janssen vaccines worldwide, incidence of severe Coronavirus Disease 2019 (COVID-19) infection has significantly decreased. In spite of their undisputed role in reducing the severity of the disease and reduction of the disease burden in the community, there have been case reports of serious side effects with these vaccines. We aim to describe a case report of myocarditis following administration of the Janssen vaccine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…However, there have been recent reports of myocarditis following adenovirus vector COVID‐19 vaccines as well. 5 , 6 , 7 , 8 , 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there have been recent reports of myocarditis following adenovirus vector COVID‐19 vaccines as well. 5 , 6 , 7 , 8 , 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…This patient received symptomatic treatments which lead to his discharge following clinical improvement. 5 , 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated post-COVID-19 vaccine-related myositis [12][13][14]. There was also cardiovascular involvement including myocarditis and myopericarditis [15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, relatively similar rates of myocarditis occurrence would be expected among receivers of adenoviral vector-based platforms. the currently available evidence presents a rather solid counterargument against this scenario; while cases of myocarditis/pericarditis in association with administration of the ChAdOx1 vaccine (Vaxzevria, AstraZeneca) have also been reported, they do not seem to occur more frequently than expected in the absence of vaccination [ 23 , 24 ], while there is so far one published only 1 case reported after Janssen Ad26.COV2.S [ 25 ]. Furthermore, mRNA strands are immunogenic and may themselves trigger an immune response directed against cardiomyocyte epitopes or adversely influence the myocardium in the frame of an exaggerated systemic reaction [ 22 ].…”
mentioning
confidence: 99%